Effect of pyrolysis conditions on characteristics and fluoride adsorptive performance of bone char derived from bone residue - Shahid, Muhammad Kashif; Kim, Jun Young; Shin, Gwyam; Choi, Younggyun (Journal of Water Process Engineering, 2020)
The high cost and environmental issues associated to the fluoride removal technologies as well as their continuous and excessive applications display several challenges in groundwater remediation. This study discusses the fluoride removal potential of bone char prepared from the bone residue. The influence of pyrolysis conditions on the physiochemical properties of the bone char is examined. The bone char synthesized under modest conditions was characterized using a field emission scanning electron microscope, energy dispersive X-ray spectroscopy, X-ray photoelectron spectroscopy and X-ray diffraction. It was found that fluoride adsorption declines with rising the calcination temperature. The bone char samples prepared under N2 environment indicated higher adsorption as compared with the samples prepared under air environment. 4.29 mg of fluoride is adsorbed on 1 g of bone char prepared at 350 °C under N2 environment while, this value was dropped to 2.91 mg g−1 when bone char is synthesized at 700 °C. However, under air environment, the adsorption was 3.63 and 0.16 mg g−1 for bone chars prepared at 350 and 700 °C, respectively. The packed bed columns were operated with different size of particle (150–425 μm) and EBCT (0.5 & 1 h). Columns effectively treated the fluoride containing influent (10 mg L−1) and achieved acceptable level in a short EBCT. This study displayed the great potential of bone char usage in fluoride affected areas.
Keywords: Adsorption; Bone char; Fluoride; Groundwater; Hydroxyapatite